2014
DOI: 10.3314/mmj.55.e63
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Fungemia with Scedosporium prolificans in a Patient with Acute Myeloid Leukemia

Abstract: Scedosporium prolificans (S. prolificans) is a type of mold, which rarely affects immunocompromised people. We treated a 71-year-old woman with acute myeloid leukemia (AML-M5a) with low-dose cytarabine, acralubicin, and filgrastim as the induction therapy. On day 7 after the initiation of chemotherapy, she became febrile and agranulocytic, and developed anal pain ; therefore, we discontinued the chemotherapy on day 8. Broad-spectrum antibiotics, micafungin, and then liposomal amphotericin B were ineffective. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Scedosporiosis is a rare complication of hematological malignancies, particularly acute myeloid leukemia (AML). 252,258,278,285,[294][295][296][297] In 1995, four cases of scedosporiosis (all fatal) were reported in neutropenic patients with hematological malignancies in Spain. 298 In 1997, Spanish investigators reported 16 cases of scedosporiosis seen at six centers between 1989 and 1994; 15 had hematological malignancy.…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…Scedosporiosis is a rare complication of hematological malignancies, particularly acute myeloid leukemia (AML). 252,258,278,285,[294][295][296][297] In 1995, four cases of scedosporiosis (all fatal) were reported in neutropenic patients with hematological malignancies in Spain. 298 In 1997, Spanish investigators reported 16 cases of scedosporiosis seen at six centers between 1989 and 1994; 15 had hematological malignancy.…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…S. prolificans is resistant to most clinically available antifungal agents (3, 6). As such, S. prolificans infection is often fatal after dissemination to multiple organs.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocompromised or immunosuppressed patients, including patients with HIV, organ transplant recipients, hematopoietic stem cell transplant recipients, and patients with hematologic malignancies, are more likely to be infected with Scedosporium (3, 4, 6). However, one study reported that 21% of 270 patients with Scedosporium infection were immunocompetent (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical utility of this test is well summarized by meta-analyses [ 56 , 57 ] and demonstrates generally good sensitivity and specificty (for any IFD) in various patient populations. This has typically included a small number of patients with Scedosporium and L. prolificans infections and is supported by the detection of BDG in serum in reports of Scedosporium brain abscess and L. prolificans fungemia [ 58 , 59 , 60 ]. The serum BDG test may thus be a useful diagnostic adjunct.…”
Section: Microbiological Diagnosismentioning
confidence: 99%